Evaluation of the quality of HIV/AIDS counselling and testing program at George Stegman ARV Clinic - Monageng, Regina Mmabo (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2008.